The Integrative Sustainability Business Mentoring Model for Politicize Creative Economy Business Actors in Meeting Tax Compliance - Susyanti, Jeni; Askandar, Noor Shodiq; Dahlan, Ahmad (Jurnal Politik Indonesia: Indonesian Political Science Review, 2021)
Â The creative economy is becoming important because current development is faced with the ability of the state to synergize tax administration, taxpayers, through the support of political commitment, social, cultural, and economic conditions to create the success of national taxation. Taxation is the backbone of state revenue and the creative economy as a forum for the younger generation to channel their creativity in doing business and building the country. The purpose of this research is to conduct a cluster of problematic creative economy business actors; know the integrative sustainable business assistance model for creative economy business actors; know integrative sustainability actions to increase taxpayer compliance, and politicize creative economy business actors. In-depth interviews and documentation obtained data. Determination of data sources using random sampling. The data validity used source triangulation. The data analysis technique used a data analysis model according to Miles and Huberman. The results showed that there are problematic clusters of creative economy business actors divided into culinary services and culinary goods. The need for an integrated sustainable business assistance model for creative economy business actors that involves intellectuals, business people, creative economy community, government, mass media - social media, and resources. Integrative sustainability actions to improve taxpayer compliance and politicize creative economy business actors through expanding tax training with the Business Development Services (BDS) Program, enactment of PP 23 of 2018, simplifying legislation for creative economy business actors with the enactment of the Omnibus Law, to the local government Omnibus Law give authority to the chief executive to provide fiscal incentives to business actors to increase taxpayers.